Nationalism and Identity in the Tenth Anniversary Exhibition in 1958 (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2025)
In this article, I discuss the Tenth Anniversary Exhibition held in Jerusalem in the summer of 1958, which was intended to showcase the achievements of the State of Israel in its first decade. The exhibition has not yet received a full and comprehensive scholarly account. Its presence in Israeli culture is minimal, and it appears not to have left a deep impression on its visitors in comparison to national and commercial exhibitions held in Israel and worldwide during those years which served as important tools for shaping national identity and collective memory. Here I reconstruct the exhibition, analyze its propaganda goals, and consider whether it met the ambitious objectives set by its organizers. The exhibition was an initiative of the Israeli government, as part of the Tenth Anniversary celebrations held nationwide. There were debates among the mayors of Israel’s major cities regarding its location, style, and content until the government decided to hold it in Jerusalem, the capital. The organizers sought to give it a festive character and imbue it with content that would inspire a sense of exaltation among its visitors. The contemporary press was enthusiastic about the exhibition, but soon after its opening – and especially following it – reports emerged describing boredom, incomplete displays, complaints about the venue, low visitor turnout, organizational failures, and poor planning. Using archival documents, the exhibition catalog, and contemporary media reports, I analyze the exhibition’s content in light of the political, cultural, and social processes of the 1950s in Israel. I highlight the gap between the exhibition’s goals and its actual impact, emphasizing the aims its planners envisioned for it as a tool to promote the Zionist ethos and national identity in the state’s first decade.
Keywords: collective memory; first decade; Jerusalem; national exhibition; national identity